Pertanggungjawaban Hukum Pejabat Negara dalam Tindak Pidana Korupsi Berdasarkan Sistem Peradilan Pidana di Indonesia - I Nyoman Trisna Wahyu Mahaputra; Sofa Laela (Decisio: Jurnal Ilmiah Hukum, 2025)
Corruption involving state officials remains a critical issue in Indonesia, significantly undermining public trust and national development. Despite the existence of anti-corruption regulations, many officials exploit legal loopholes, resulting in ineffective law enforcement. The complexity of Indonesia’s criminal justice system, coupled with political interference, often hampers the prosecution of corrupt officials. Thus, analyzing the legal accountability of state officials in corruption cases is crucial to strengthening legal enforcement mechanisms. This study employs a qualitative research method with a normative legal approach, focusing on the analysis of statutory regulations and judicial decisions. Data collection is conducted through a comprehensive literature review, including primary legal sources such as laws, court rulings, and secondary references like academic journals and legal commentaries. The findings indicate that legal accountability for corrupt state officials encompasses three main aspects: criminal, civil, and administrative liability. However, the effectiveness of Indonesia’s criminal justice system remains questionable due to inconsistent law enforcement, lack of institutional coordination, and the influence of political power. The research highlights the necessity for legal reform, particularly in strengthening institutional independence and public participation in corruption eradication. Strengthening transparency and accountability within the judiciary is essential to ensure that corrupt officials receive appropriate sanctions and to restore public confidence in the legal system.